Child rearing practices of Filipino urban mothers relationship to children's cognitive development - Umali-Razon, Perpetua G. (Philippine Journal of Psychology, 1981)
The study investigated the child rearing patterns of Filipino urban mothers and the relationship of child rearing practices to the cogntive development of children. It also determined the relationship of family structure, mother's work status, socio-economic status of the family, sex and birth order of the child to child rearing and children's cognitive performance. One hundred fifty mother-child pairs were used as subjects. The child-rearing practices of each mother were investigated through an interview schedule. Three child-rearing dimensions were applied; love-hostility, autonomy-control, and cognitive growth. The cognitive performance of the child was determined through a test of 10 items on cognitive tasks which included conservations, classification and seriation.